1963
DOI: 10.1111/j.1365-2494.1963.tb00329.x
|View full text |Cite
|
Sign up to set email alerts
|

Strip Grazing Versus Paddock Grazing Under Tropical Conditions

Abstract: A sixteen-month trial is described where strip grazing was compared with a 3-paddock system of rotational grazing. 7i acres of grazing was allotted to each group, but the strip-grazed cattle were limited to half an acre of grazing while the paddock-grazed beasts had access to 24 acres at a time. The pasture was rested for 6 weeks after strip grazing and 2 weeks after paddock grazing.Treatment effects were found to vary with the pasture conditions. The paddock-grazed cattle benefited most when average grass qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

1966
1966
1991
1991

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
0
2
1
Order By: Relevance
“…Over the 2-year period the average liveweight gain was a little below 200 Ib per acre per annum. This is less than that reported by Joblin (8), most probably because of the fixed stocking rate used and because a proportion of the pastures were in their second and third year of A severe dry period early in 1961 also reduced production.…”
Section: Resultscontrasting
confidence: 66%
“…Over the 2-year period the average liveweight gain was a little below 200 Ib per acre per annum. This is less than that reported by Joblin (8), most probably because of the fixed stocking rate used and because a proportion of the pastures were in their second and third year of A severe dry period early in 1961 also reduced production.…”
Section: Resultscontrasting
confidence: 66%
“…Trials have shown that rotational grazing is desirable to maintain botanical composition and to achieve good liveweight gains (18,26). A 3-paddock system is recommended in which each paddock is grazed for 2 weeks and rested for 4 weeks.…”
Section: Pasture Utilizationmentioning
confidence: 99%
“…Night grazing, particularly at times of pasture shortage, has been shown by Joblin (17) to be necessary to achieve optimum animal production, and night paddocking has obvious advantages over the present system of returning stock to a small enclosure, or boma, at sunset to protect them from predators. Trials have shown that rotational grazing is desirable to maintain botanical composition and to achieve good liveweight gains (18,26). A 3-paddock system is recommended in which each paddock is grazed for 2 weeks and rested for 4 weeks.…”
Section: Pasture Utilizationmentioning
confidence: 99%